Rapid weight loss among adolescents participating in competitive judo - Berkovich, B.-E.; Eliakim, A.; Nemet, D.; Stark, A. H.; Sinai, T. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Athletes competing in individual sports such as judo are categorized by weight. Before competitions, weight cutting is common. This cross-sectional study was designed to characterize and determine the prevalence of rapid weight loss (RWL) among adolescent judo competitors. Male athletes aged 12- to 17-years old (N = 108) were recruited from local judo teams. Each participant completed a validated questionnaire regarding RWL practices. Anthropometric measurements were also performed. Average age was 14.6 ± 1.6 years and all participants were of normal body mass index (BMI). RWL was practiced by 80% of the athletes before competition, beginning at an average age of 12.5 ± 2.2 years with the highest prevalence (~94%) in the oldest group of judoka (16-17.9 years). Precompetition weight loss duration was 8 ± 5.4 days, with an average weight reduction of 1.5 ± 1.1 kg. The number of weight loss efforts per athlete in the past season was 2.8 ± 2.2. RWL was achieved by increased physical activity (82.6%), skipped meals (56.3%), or fasting at least once (47%). Two-thirds of the athletes indicated that their coaches were the most influential figure in their decision to lose weight before competition. RWL is highly prevalent in adolescent judo competitors. The methods used by these athletes can potentially lead to significant health risks including compromised nutritional status, diminished physical performance and impaired growth and development. It is of great importance to insure that those who guide young adults in weight loss for competitive sports have the knowledge and understanding to make safe recommendations and appropriate decisions regarding achieving specific weight goals.